DSGE Models for the South African Economy - Abbas_A, Ahmed (School of Economics, 2024)
Dynamic stochastic modelling is relatively a new exercise in developing countries including South Africa. We use stochastic models to reproduce stylized facts of business cycles in South Africa. The basic neoclassical model and a model with indivisible labour are used to replicate the documented facts from the data. A model with variable capacity utilization and investment specific shocks is also used to reproduce facts about the manufacturing sector in South Africa. The models fair reasonably well in replicating volatilities of certain variables, but investment remains over-volatile in all the models. However, the South African labour market remains the hardest to replicate amidst well documented inflexibility